2007
DOI: 10.2136/sssaj2004.0376
|View full text |Cite
|
Sign up to set email alerts
|

Emission of Nitrogen Gas, Nitrous Oxide, and Carbon Dioxide on Rehydration of Dry Feathermosses

Abstract: Two experiments were conducted to examine the fate of N in feathermosses when mosses were dehydrated and then rewetted. In the first experiment, dry feathermoss shoots were sealed in containers where the N2 was replaced by He. After rewetting and incubating for 20 h, gas in the containers had significant amounts of N2 and N2O and had elevated levels of CO2 compared with mosses maintained in a moist condition or dried mosses that had not been rewetted. In the second experiment, samples of feathermoss were subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…An important finding in terms of the N balance of the ecosystem was that, during the first 4 years of the experiment, 15 N losses from the moss layer were not compensated for by a corresponding increase in recovery rates in any other compartment. These losses accounted for more than 30% of the total 15 N applied and suggest that N losses from the moss layer in gaseous forms are very likely (Startsev and Lieffers, 2007 ; for a further discussion of this aspect see paragraph ‘Leaching losses and putative flows’ below). In contrast, the largely constant recovery rates found from 2010 onwards point to a conservative N cycling with marginal 15 N losses from the N pool of the ecosystem in the long term (Tye et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important finding in terms of the N balance of the ecosystem was that, during the first 4 years of the experiment, 15 N losses from the moss layer were not compensated for by a corresponding increase in recovery rates in any other compartment. These losses accounted for more than 30% of the total 15 N applied and suggest that N losses from the moss layer in gaseous forms are very likely (Startsev and Lieffers, 2007 ; for a further discussion of this aspect see paragraph ‘Leaching losses and putative flows’ below). In contrast, the largely constant recovery rates found from 2010 onwards point to a conservative N cycling with marginal 15 N losses from the N pool of the ecosystem in the long term (Tye et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the observed accumulation of N, the first 4 years of the experiment (2007–2010) also exhibited a considerable loss of 15 N. Tracer mass balances suggest that this loss was attributable to a leak of N from the moss layer in gaseous forms (Startsev and Lieffers, 2007 ). High N losses from bryophyte layers due to denitrification have been found for different species and ecosystems, and increase with increasing humidity (e.g., with water saturation of the moss layer after precipitation events), temperature, and N deposition (Laverman et al, 2000 ; Opelt and Berg, 2004 ; Lenhart et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Once hydrolyzed, the elevated pH following urea hydrolysis (Malhi et al 1992) likely created conditions that promoted some volatilization of NH 3 from substrates with inherently high pH or low buffering capability (Fan and Mackenzie 1993). Volatilization of NH 3 or denitrification (Startsev and Lieffers 2007) may explain the 19% of added N that could not be accounted for in either the substrate or leachate in the growth chamber experiment.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that fracturing of the substrate during handling might have increased water channeling through the litter, thereby make the leaching less effective during the larger watering events. Continuously moist conditions may have increased the nutrients immobilization rate in the substrate (Compton and Boone 2002) or promoted denitrification (Startsev and Lieffers 2007) as under those conditions N transfer to the leachate was low.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, these locations varied in the amount of plant debris input and its quality. Startsev and Lieffers [68] showed that decomposing litter generally trapped in the bryophyte layer contributed to the total CO 2 production, and provided bryophytes with a source of easily available nutrients and carbohydrates. In our study, the total amount of plant debris input was greater in the southern treed areas where trees were bigger and more productive, which was also an important factor in southern treed peat plateaus.…”
Section: Quantitative Relationships Between Nce and Er And Climate Vamentioning
confidence: 99%